Chemiluminescence: From mechanism to applications in biological imaging and therapy. Issue 6 (28th October 2021) - Wang, Zhijia; Huang, Jiaguo; Huang, Jingsheng; Yu, Bingran; Pu, Kanyi; Xu, Fu‐Jian
Abstract: Chemiluminescence (CL) is an emission phenomenon induced by chemical reaction. Different from the photoluminescence, CL is free from external excitation source, which is expected to show great advantages such as higher signal‐to‐background ratio (SBR) in bioimaging, and deeper tissue penetration in photodynamic therapy (PDT). This review introduces the theoretical aspects of CL mechanism, such as classification, energy consideration and chemiexcited/photoexcited states. Application of CL in bioimaging is highlighted. In particular, the approaches to modulate the brightness and the wavelength of CL are summarized, which are two fundamental parameters in bioimaging. Finally, the application of CL in PDT is introduced. The potential challenges and perspectives of CL in bioimaging and therapy are also discussed. Abstract : This review introduces the theoretical aspects of CL mechanism, such as classification, energy consideration and chemiexcited/photoexcited states. Application of CL in bioimaging is highlighted. In particular, the approaches to modulate the brightness and wavelength of CL are summarized along with the application of using CL as external excitation source for PDT.